Directions in Ornamental Herbaceous Plant Selection in the Central European Temperate Zone in the Time of Climate Change: Benefits and Threats - Marta Joanna Monder; Andrzej Pacholczak; Małgorzata Zajączkowska (Agriculture)
Extreme weather events, considered to be the most destructive natural hazards connected with rapid climate changes in the temperate zone of Europe, necessitate swift adjustments to the selection of ornamental plants for cultivation in multi-stress urbanized areas, public greeneries, and gardens. Moreover, given the rising average air temperature and prolonged growing season, as well as the delay and shortening of the dormancy period, plant phenology is subject to significant alternations. Herbaceous plants fulfill most elements of ecosystem service, e.g., they may enhance biodiversity in climate-warming conditions and create a favorable environment for trees in cities. In this work, we consider the advantages and disadvantages of the dissemination or introduction of annuals and perennials. We draw attention to species rarely or never known to have been cultivated in Europe, which currently occupy hotspots with the highest biodiversity value, including (i) the Mediterranean Basin, (ii) the Caucasus, (iii) Irano-Anatolian, (iv), and the mountains of Central Asia. We emphasize the importance of protecting threatened taxa through safe ex situ cultivation. Ornamentals should be characterized not only by aesthetic values but also by their ability to adapt to environmental changes. However, bearing in mind that horticulture is an important source of invasive alien species, further research assessing the ecological threats and advantages should be conducted.